To the question of shape stability of panel blanks - Bilyy, Yaroslav; Grytsak , Stepan (Forestry, Forest, Paper and Woodworking Industry, 2013)
The influence humidity of veneer on the stability shape cabinet furniture panel blanks in the process veneering of MDF panels are investigate